Anti-IL-17A antibody-associated de novo vitiligo: Case report and review of literature - Su, Hsing-Jou; Chan, Yu-Pei; Shen, Peng-Chieh; Ku, Cheng-Lung; Ng, Chau Yee (Frontiers in Immunology, 2023)
Interleukin (IL)-17 inhibitor is a biological therapy approved for moderate to severe psoriasis and psoriatic arthritis. The common adverse events of IL-17 inhibitor include injection site reaction, infections, nasopharyngitis, and headache. However, vitiligo associated with the use of IL-17 inhibitors was rarely reported in the previous literature. Here we described a woman who developed de novo vitiligo after 4 months of IL-17A inhibitor treatment for psoriasis and psoriatic arthritis. Upon discontinuation of IL-17A inhibitor and shifting to a broader T cell inhibitor—cyclosporine, our patient had control of both psoriasis and vitiligo and achieved 75% repigmentation after 3 months of oral cyclosporine without phototherapy. Due to the increasing use of anti-IL-17 biologics in psoriasis patients, clinicians should inquire about vitiligo’s history before treatment and inform patients of the possible adverse effects.